2019
DOI: 10.1177/1363459319851545
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating exercise as medicine: Narratives from people with type 2 diabetes

Abstract: The dominant notion that exercise is medicine puts a strong normative emphasis on individual responsibility for participation in sport and physical activity. The aim of this article was to explore how people with type 2 diabetes, a condition strongly linked to lifestyle behaviour both in origin and in management, translate this notion into their daily life. Based on a critical narrative analysis of stories of 18 Dutch people diagnosed with type 2 diabetes collected between 2012 and 2016, we found a range of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This perception may, however, not be entirely in line with the patients’ actual perspective. Some studies have conducted qualitative studies in patients on the perception of E=M prescription 37 38. Some of the barriers, such as lack of knowledge, lack of time and lack of motivation, were indeed mentioned by patients with osteoporosis to hamper a physically active lifestyle 38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This perception may, however, not be entirely in line with the patients’ actual perspective. Some studies have conducted qualitative studies in patients on the perception of E=M prescription 37 38. Some of the barriers, such as lack of knowledge, lack of time and lack of motivation, were indeed mentioned by patients with osteoporosis to hamper a physically active lifestyle 38.…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of discussing E=M on the relationship between patient and clinician, that some clinicians reported, may differ between patient groups. In patients with osteoporosis, this did not seem to be a problem,38 but many patients with type 2 diabetes responded defensively when asked about their physical activity pattern 37. The patients reported that they usually turned to their general practitioner for exercise advice,38 which indicates that not discussing a physically active lifestyle with clinicians may be a missed opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Stuij et al explored how people with type 2 diabetes translate the notion of exercise as medicine into their daily lives and found that they employed a range of strategies to negotiate this translation ranging from (almost) total acceptance to resistance. 35 The study also revealed mostly negative experiences with care and professional support were related to sport or physical activity participation. This differs from our findings that pointed to a generally positive rapport between people living with multimorbidity and healthcare professionals.…”
Section: Discussionmentioning
confidence: 87%
“…This should go further than types of words used (e.g., “negative,” “neutral,” or “positive”) and counselling techniques (e.g., aimed at motivation or empowerment), as other studies suggest (Pont, Puhl, Cook, & Slusser, ). Reflection requires professionals to examine their own normative notions about body weight and related lifestyle behaviour and the impact of these notions on their care relationships (Stuij, Elling, & Abma, ; van Ewijk, van der Vet, & de Waal, ).…”
Section: Discussionmentioning
confidence: 99%